Hyperglycemia Promotes TMPRSS2-ERG Gene Fusion in Prostate Cancer Cells via Upregulating Insulin-Like Growth Factor-Binding Protein-2 - Holly, Jeff M. P.; Broadhurst, Jessica; Mansor, Rehanna; Bahl, Amit; Perks, Claire M. (Frontiers in Endocrinology, 2017)
Background Epidemiologic evidence shows that obesity is associated with a greater risk of aggressive prostate cancer (PCa) and PCa-specific mortality and this is observed mainly in men with the TMPRSS2-ERG gene fusion. Obesity is often associated with comorbid conditions such as type 2 diabetes and hyperglycemia: we investigated whether some of the exposures associated with disturbed metabolism can also affect the frequency of this gene fusion. Methods Fusion was induced in LNCaP PCa cells in normal or high levels of glucose, with or without insulin-like growth factor binding protein-2 (IGFBP-2) silenced or the presence of insulin-like growth factor-1 (IGF-I), insulin, or epidermal growth factor (EGF). RNA was extracted for analysis by nested PCR. Abundance of IGFBP-2, γH2AX, DNA-dependent protein kinase catalytic subunit (DNAPKcs), and β-actin were analyzed by Western immunoblotting. Results Our data suggest that hyperglycemia-induced IGFBP-2 increased the frequency of the gene fusion that was accompanied by decreased levels of DNAPKcs implying that they were mediated by alterations in the rate of repair of double-strand breaks. In contrast insulin, IGF-I and EGF all decreased gene fusion events. Conclusion These novel observations may represent a further mechanism by which obesity can exert an effect aggravating PCa progression.